HOW COVID-19 ENHANCED MY DIGITAL LITERACY: REFLECTIONS AND TIPS ON DIGITAL TEACHING TOOLS - Mamajanova, Dildora (Журнал иностранных языков и лингвистики, 2021)
Abstract The following articles outlines the author’s experiences of using various teaching tools used in the emergency online teaching resulting from the pandemic. Some recommendations and information concerning online teaching platforms, tools for providing feedback and holding discussions, and different digital games are provided.